Cultura y participación juvenil en las agrupaciones políticas del cantón Pasaje en el año 2021 - Farez Salinas, José Luis; Vinces Rodríguez, Marco Vinicio (Machala : Universidad Técnica de Machala, 2022)
The research work on the culture and youth participation in the political groups of the Pasaje canton for the period 2021, focuses on the levels of political participation of the youth of the Pasaje canton and the incidence of political parties and movements to involve youth in electoral processes. The registration of young people in political cadres will allow their empowerment in the local political system, parties and movements are spaces to integrate new political leaders, with a view to strengthening participation in democratic processes and in the exercise of citizenship. The research aims to diagnose the importance of the culture and participation of young people in the political groups of the Pasaje canton. In addition, specifically to determine the impact of the level of culture and participation of young people in political groups; establish the factors that limit the incorporation and participation of young people in the candidacies of sectional governments; identify the strategies used by political organizations to select candidates for the local political process, and specify the purposes of the political groupings to promote training schools for young people. The methodological approach that guides the research is mixed quantitative - qualitative and the epistemological approach is inductive empirical, the study is theoretically based on the functionalist structural macrosociological approach that allows analyzing the different State institutions and the functions they perform in the political-administrative space, In addition, it allows describing the functions of political movements and parties, and their leaders with respect to institutional organization, community leadership and the inclusion of young people in electoral processes. The techniques used in the field research are the survey aimed at young people and in-depth interviews for political leaders, whose results allow answering the questions and objectives set, This presupposes a deep analysis to arrive at interpretations about the participation of young people in communities and social groups, their interest in performing in the political area, the problems that limit political incorporation and their participation as citizens for the solution of problems. of the rural and urban environment of the canton. Young people appreciate that local politics promoted by institutions is bad and that political groups generate distrust towards them, In addition, the main purpose of the parties and movements is political interests, causing a weak incorporation and inclusion of youth in political activism. It is determined that the majority of young people avoid working professionally in politics, considering getting involved in teaching, medicine, engineering and business, that is why from academic spaces there must be political training that guides participation in the public administration of the canton. to solve the problems that arise in the passenger society. Based on the results achieved, it has been possible to demonstrate the need to undertake an intervention proposal entitled Integration Programs in young passengers that motivate participation in the perspective of developing social, economic and political projects. This program is aimed at developing the orientation, encouragement, commitment and participation of young people in social, cultural, economic and political matters, involving them as leaders and actors of new proposals for participation and social solutions.
El trabajo de investigación sobre la cultura y participación juvenil en las agrupaciones políticas del cantón Pasaje para el periodo 2021, enfoca los niveles de participación política de los jóvenes del cantón Pasaje y la incidencia de los partidos y movimientos políticos para involucrar a la juventud en los procesos electorales. La inscripción de jóvenes en los cuadros políticos permitirá el empoderamiento de los mismos en el sistema político local, los partidos y movimientos son espacios para integrar a nuevos líderes políticos, en perspectiva de fortalecer la participación en los procesos democráticos y en el ejercicio de la ciudadanía. La investigación tiene por objetivo diagnosticar la trascendencia que tiene la cultura y participación de los jóvenes en las agrupaciones políticas del cantón Pasaje. Además, de manera específica determinar el impacto que tiene el nivel de cultura y participación de los jóvenes en las agrupaciones políticas; establecer los factores que limitan la incorporación y participación de los jóvenes a las candidaturas de los gobiernos seccionales, identificar las estrategias que utilizan las organizaciones políticas para la selección de los candidatos al proceso político local, y especificar los propósitos de las agrupaciones políticas de fomentar las escuelas de formación para los jóvenes. El enfoque metodológico que orienta la investigación es mixto cuantitativo – cualitativo y el enfoque epistemológico es el empírico inductivo, el estudio se fundamenta teóricamente en el enfoque macrosociológico estructural funcionalista que permite analizar las diferentes instituciones del Estado y las funciones que cumplen en el espacio político administrativo, además, permite describir las funciones de los movimientos y partidos políticos, y sus dirigentes con respecto a la organización institucional, liderazgo comunitario y la inclusión de los jóvenes en los procesos electorales. Las técnicas utilizadas en la investigación de campo son la encuesta dirigida a los jóvenes y las entrevistas en profundidad para los dirigentes políticos, cuyos resultados obtenidos permiten responder las preguntas y objetivos planteados, esto presupone un análisis profundo para llegar a interpretaciones acerca de la participación de los jóvenes en las comunidades y agrupaciones sociales, su interés por desempeñarse en el área política, los problemas que limitan la incorporación política y su participación como ciudadanos para la solución de los problemas del entorno rural y urbano del cantón. Los jóvenes aprecian que la política local fomentada por las instituciones es mala y las agrupaciones políticas generan desconfianza hacia los mismos, además, el principal propósito de los partidos y movimientos son los intereses políticos provocando una débil incorporación e inclusión juvenil en el activismo político. Se determina que la mayoría de los jóvenes evita desempeñarse profesionalmente en la política, considerando involucrarse en la docencia, medicina, ingeniería y empresarial, por eso desde los espacios académicos debe existir una formación política que oriente a la participación en la administración pública del cantón, para solucionar los problemas que se presentan en la sociedad pasajeña. En base a los resultados alcanzados se ha logrado evidenciar la necesidad de emprender una propuesta de intervención titulada Programas de integración en los jóvenes pasajeños que motiven a la participación en perspectiva de desarrollar proyectos sociales, económicos y políticos. Este programa se direcciona en desarrollar la orientación, incentivación, compromiso y participación de los jóvenes en asuntos sociales, culturales, económicos y políticos, que los involucre como líderes y actores de nuevas propuestas de participación y solución social.
Keywords: PARTICIPACION JUVENIL; ORGANIZACION POLITICA; CUADRO POLITICO; PROCESO ELECTORAL